The relationship between multiculturalism values and leadership in digital islamic education: a quantitative study - M Hurmaini; J.M Ekafitrianda; Nasir; Yudi Kurniawan (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This study explores the implementation of multiculturalism values and leadership within the context of digital Islamic education among university students. Employing a quantitative research approach, data were collected from a sample of 300 Islamic Education students selected from a total population of 621 at a public university. The primary aim was to investigate the relationship between students’ multicultural values and their leadership abilities in digital learning environments. The findings reveal a significant positive correlation between multicultural awareness and effective leadership, indicating that students who are more attuned to multicultural values tend to exhibit stronger leadership skills. These results highlight the importance of integrating multicultural competencies into educational practices. As a result, the study recommends that curriculum development in Islamic education should incorporate training and content that foster multicultural leadership to enhance the effectiveness of digital learning